Utility of Repeat Head Computed Tomography for Intracranial Hemorrhage After Trauma and Importance of Direct Patient Care. Issue 5 (September 2016) - Zimmermann, Mary Ellen; Brown, Zachary; Matemavi, Praise; Melnic, Gloria; Sample, Jason
Abstract : At many institutions, it is common practice for trauma patients with traumatic intracranial hemorrhage (ICH) to receive routine repeat head computed tomographic (CT) scans after the initial CT scan, regardless of symptoms, to evaluate progression of the injury. The purpose of this study was to assess quantifiable risk factors (age, anticoagulation, gender) that could place patients at greater risk for progression of injury, thus requiring surgical intervention (craniotomy, craniectomy) for which serial CT scanning would be useful. From January 2014 to June 2015, a total of 211 patients presented with traumatic ICH and 198 were eligible for inclusion. Twenty-six patients required operative intervention for ICH. One of 26 patients went to the operating room as a result of repeat head CT scans without associated mental status change, change in neurological examination, or associated symptoms such as nausea or vomiting. Significant changes in patient management due to routine repeat CT scans were not observed. There were no statistically significant risk factors identified to place patients at higher risk for progression of disease. The data from this analysis emphasized the importance of nursing care in identifying and relaying changes in patient condition to the trauma team.